GENERASI CERDAS DIGITAL: TINJAUAN LITERATUR SISTEMATIS PELUANG DAN TANTANGAN LITERASI DIGITAL DI SEKOLAH DASAR - Salama, Mahi Sultan; Wuriningsih, FR.; Kristiyuana, Kristiyuana; Intania, Belita Yoan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the digital literacy practices of Indonesian elementary school students in overcoming technology access gaps. A systematic literature review was conducted across Scopus, Web of Science, and Google Scholar for publications from 2020 to 2025. Following PRISMA guidelines and using narrative synthesis, 10 empirical studies were selected based on their focus on student-centered strategies under constrained infrastructure. Findings reveal that students employ collaborative scheduling of school computer labs and community centers; leverage personal smartphones with peer-to-peer sharing via Bluetooth and messaging apps; integrate offline materials such as printed modules and USB flash drives; and utilize “lite” versions of digital quiz platforms for formative assessment. Additionally, single-download interactive content (e.g., PhET simulations, Extended Reality recordings) is repeatedly accessed offline. These adaptive practices underscore the critical role of teachers in designing hybrid learning packages and highlight the need for supportive policies standardized offline modules, teacher training in blended pedagogy, and development of bandwidth-optimized digital platforms to ensure inclusive and sustainable digital literacy.